Evolution of corrosion products on ASTM A36 and AISI 304L steels formed in exposure to molten NaNO3–KNO3 eutectic salt: Electrochemical study. (March 2022) - Pineda, Fabiola; Walczak, Magdalena; Vilchez, Franco; Guerra, Carolina; Escobar, Rodrigo; Sancy, Mamié
Abstract: Thermal energy storage uses molten salt as a heat transfer fluid implies a high corrosion risk. In this work, ASTM A36 and AISI 304L steel, exposed to solar salt at 390 °C for 21 days, were studied by electrochemical impedance spectroscopy. The results were validated by mass gain and the characterization of corrosion products. Carbon steel revealed a porous behavior related to the formation of corrosion products based on iron oxides, as described the De Levie´s theory, whereas stainless steel showed the formation of a passive multilayer of iron and chromium oxides, which was adjusted to the Power-law model. Highlights: The corrosion behavior in real-time of two steel in molten was studied by Impedance. The carbon steel develops a porous corrosion product. The stainless steel develops a passive multilayer. The real-time tracking results reveal higher accuracy than post-exposure techniques.